Aggression in intimate relationships: an examination of female dominance and aggression - Edalati, Ali; Redzuan, Ma'rof (Canadian Center of Science and Education, 2010)
Several researches have shown that both men and women involve in intimate partner aggression within their relationship. In relation to this, this study attempts to examine the relationship between female’s dominance (disparagement, restrictiveness, and authority), and their aggression (physical and psychological). The study employed survey design. It was carried out among a sample of 337 married women (wives) in Shiraz City, Iran, who were identified as engaging physical and psychological aggressions. Conflict Tactics Scale (CTS) was employed to measure aggression; meanwhile dominance was measured using Hamby Dominance Scale (HDS). The study employed correlations test to determine the relationships between variables, and Regression Analysis was used to identify the factors that contribute aggressions. The study found that there were positive significant relationships between dominance (disparagement and restrictiveness) and female physical aggression. There were also positive significant relationships between dominance (disparagement, restrictiveness and authority) and psychological aggressions. The result of Regression Analysis showed that the selected factors contributed 10.9% in explaining the psychological aggression. However, two predictor variables of authority and disparagement were found to be significant in explaining psychological aggression. These findings imply that dominance is an important variable to be considered in the analysis of intimate partner aggression.